PEMBUATAN DAN UJI MUTU FISIK SEDIAAN SALEP DARI EKSTRAK ETANOL KULIT BUAH PISANG BARANGAN (Musa Acuminata colla) - Samosir, Sri Rezeki; Adhe Christie Immanuel (Universitas Imelda Medan, 2022)
Skin Fruit Banana goods (Musa acuminate Colla) can used as ingredient blocker bacteria. Research this aim for knowing activity antibacterial preparation ointment from extract skin fruit banana goods (Musa acuminate colla) against Staphylococcus aureus. Method Study this conducted Experimental, extract obtained with use method maceration with solvent 96% followed after that the extract was concentrated with rotary evaporator. Ethanol obtained tested Phytochemicals. The results of screenings showed that all of the extracts from skin fruit banana contained flavonoid, alkaloid, steroid, terpenoid and tannin, then made preparation ointment using Vaseline Album base, Adeps Lanae, Paraffin Liquid, Setyl Alcohol and preparation ointment Extract Skin Fruit Banana goods have Concentration 4%, 6%, 8%.